Contribuições da análise do comportamento para a Educação a Distância: uma análise de publicações - Giolo, Juliana Cristina de Carvalho (2016)
This study aimed to investigate the productions of Behavior Analysis and distance education in national and international journals. A search for articles was carried out by search words previously selected in www.psycinfo.com.br site. Based on selected articles were identified periodicals with publications on distance education and these were sought on the CAPES website (http://www.capes.gov.br/), so that a second search of articles could be held through the search words directly on the site of each journal. All items well located from the search words were subjected to screening, based on reading the abstracts, using as criteria: the studies were in Behavior Analysis (which made reference to concepts of the area or whose authors were known behavior analysts) and to respect the school features a distance education, presented in Decree No. 5622, in Article 1, which are: 1) educational modality in which the didactic and pedagogical mediation in the processes of teaching and learning takes place using media and information and communication technologies; and 2) students and teachers develop educational activities in different places or times. Of the 717 articles found, 40 were selected as Behavior Analysis and distance education and were categorized as variables and predefined categories of analysis. The results show that the computer was the most used technology from the 1990s, most of the participants of higher level jobs. Regarding the target behavior, most studies returned to academic skills; and the most widely used teaching procedure was CAPSI (Computer Aided Instruction Personalized Systemof). Most studies were categorized as partially the distance and dealt with the formal education. Overall, it is concluded that the number of articles on distance education and Behavior Analysis is still very small compared to the number of articles published in 25 journals analyzed